Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Numerically it seems to be true that

$$ \int_0^\infty \frac{\sin x}{\sqrt{x}}dx=\sqrt{\frac{\pi}{2}}. $$

Any ideas how to prove this?

share|cite|improve this question
Substitute $u=\sqrt{x}$ to see that this is related to Fresnel's integral... – draks ... Jul 17 '12 at 15:24

Using contour integration, we get $$ \begin{align} \int_0^\infty\frac{e^{ix}}{\sqrt{x}}\,\mathrm{d}x &=\sqrt{i\,}\int_0^\infty\frac{e^{-x}}{\sqrt{x}}\,\mathrm{d}x\\ &=\frac{1+i}{\sqrt{2}}\Gamma\left(\frac12\right)\\ &=(1+i)\sqrt{\frac\pi2} \end{align} $$ Therefore, $$ \int_0^\infty\frac{\cos(x)}{\sqrt{x}}\,\mathrm{d}x=\int_0^\infty\frac{\sin(x)}{\sqrt{x}}\,\mathrm{d}x=\sqrt{\frac\pi2} $$

About the Contour Integration

If we integrate $f(z)=\dfrac{e^{iz}}{\sqrt{z}}$ around the contour $[0,R]\cup Re^{i[0,\pi/2]}\cup i[R,0]$ as $R\to\infty$, we get that $$ \int_0^R\frac{e^{ix}}{\sqrt{x}}\,\mathrm{d}x +\int_0^{\pi/2}\frac{e^{iRe^{ix}}}{\sqrt{R}e^{ix/2}}iRe^{ix}\,\mathrm{d}x -\sqrt{i\,}\int_0^R\frac{e^{-x}}{\sqrt{x}}\,\mathrm{d}x =0 $$ because there are no singularities of $f$ inside the contour. Then because $$ \begin{align} \left|\int_0^{\pi/2}\frac{e^{iRe^{ix}}}{\sqrt{R}e^{ix/2}}iRe^{ix}\,\mathrm{d}x\right| &\le\sqrt{R}\int_0^{\pi/2}e^{-R\sin(x)}\,\mathrm{d}x\\ &\le\sqrt{R}\int_0^{\pi/2}e^{-2Rx/\pi}\,\mathrm{d}x\\ &\le\frac\pi{2\sqrt{R}} \end{align} $$ vanishes as $R\to\infty$, we have $$ \int_0^\infty\frac{e^{ix}}{\sqrt{x}}\,\mathrm{d}x =\sqrt{i\,}\int_0^\infty\frac{e^{-x}}{\sqrt{x}}\,\mathrm{d}x $$

Real Method

Substituting $u^2=x$ and applying this answer, which uses only real methods, yields $$ \begin{align} \int_0^\infty\frac{\sin(x)}{\sqrt{x}}\,\mathrm{d}x &=2\int_0^\infty\sin(u^2)\,\mathrm{d}u\\ &=2\sqrt{\frac\pi8}\\ &=\sqrt{\frac\pi2} \end{align} $$

share|cite|improve this answer
would the downvoter care to comment? – robjohn Apr 6 '14 at 9:41
I guess you take a half-circle as contour, I can't get your first equality with $\sqrt i$, could you expand please? – caub Jun 20 '14 at 23:10
@kwak: I have added a section about the contour integration mentioned. – robjohn Jun 21 '14 at 1:01
Why the second downvote? – robjohn Jun 21 '14 at 1:14
Thanks, awesome answer, the trick is to take this quarter circle – caub Jun 21 '14 at 9:11

That is a Fresnel integral.

Make the substitution $\sqrt{x}=u$. Then you get $dx=2udu$ from where

$$\int_0^\infty \sin(x) x^{-1/2} dx =2 \int_0^\infty \sin(u^2)du=2\sqrt{\frac{\pi}{8}}=\sqrt{\frac{\pi}{2}}$$

See this question for more details.

share|cite|improve this answer

Here is an another approach, which I show only a heuristic calculation:

$$\begin{align*} \int_{0}^{\infty} \frac{\sin x}{\sqrt{x}} \; dx &= \int_{0}^{\infty} \left( \frac{1}{\Gamma\left(\frac{1}{2}\right)} \int_{0}^{\infty} t^{-1/2} e^{-xt} \; dt \right) \sin x \; dx \\ &\stackrel{\ast}{=} \frac{1}{\Gamma\left(\frac{1}{2}\right)} \int_{0}^{\infty} t^{-1/2} \int_{0}^{\infty} e^{-xt} \sin x \; dx \; dt \\ &= \frac{1}{\Gamma\left(\frac{1}{2}\right)} \int_{0}^{\infty} \frac{t^{-1/2}}{1+t^2} \; dt \\ &= \frac{1}{\Gamma\left(\frac{1}{2}\right)} \int_{0}^{\infty} \frac{2du}{1+u^4}.\qquad(t = u^2) \end{align*}$$

Now it is not hard to show that

$$ \int_{0}^{\infty} \frac{2du}{1+u^4} = \frac{\pi}{\sqrt{2}}.$$

Indeed, you may use the equality

$$ \begin{align*} \frac{2 du}{1+u^4} &= \frac{2u^{-2} \; du}{u^2 + u^{-2}} = \frac{1 + u^{-2} \; du}{u^2 + u^{-2}} - \frac{1 - u^{-2} \; du}{u^2 + u^{-2}}\\ &= \frac{d\left(u - u^{-1}\right)}{\left(u - u^{-1}\right)^2 + 2} - \frac{d\left(u + u^{-1}\right)}{\left(u + u^{-1}\right)^2 - 2} \end{align*}$$

and hence deduce that

$$ \begin{align*} \int_{0}^{\infty} \frac{2 du}{1+u^4} &= \int_{0}^{\infty} \frac{d\left(u - u^{-1}\right)}{\left(u - u^{-1}\right)^2 + 2} - \int_{0}^{\infty} \frac{d\left(u + u^{-1}\right)}{\left(u + u^{-1}\right)^2 - 2}\\ &= \int_{-\infty}^{\infty} \frac{dv}{v^2 + 2} - \color{blue}{\int_{\infty}^{\infty} \frac{dw}{w^2 - 2}} \qquad \begin{pmatrix}v = u - u^{-1} \\ w = u + u^{-1}\end{pmatrix}\\ &= \frac{\pi}{\sqrt{2}} + 0. \end{align*}$$

as claimed, where the blue-colored integration is taken along the curve starting from $+\infty$ to $2$, and then turning back to $+\infty$, which makes it cancel out. Therefore we obtain the desired result.

The problem in this calculation is that the starred equality is almost unable to be justified by any simple means.

share|cite|improve this answer

From the result

$$ \int_0^\infty dx \frac{\sin x}{\sqrt x} = 2 \int_0^\infty dx \sin\left(x^2\right), $$

I'd use $\exp\left(-i x^2\right) = \cos \left(x^2\right) - i \sin \left(x^2\right)$ and

$$ \int_0^\infty dx \ \exp\left(- a x^2\right) = \frac{1}{2} \sqrt{\frac{\pi}{a}}. $$

share|cite|improve this answer

Let's start out with the following relation: $$\int_0^{\infty} \frac{\sin x}{\sqrt{x}} e^{-a x} dx = \frac{2}{\sqrt{\pi}} \int_0^{\infty} \frac{1}{1+(a+x^2)^2} dx \tag1$$ Proof of the relation $(1)$

$$\int_0^{\infty} \frac{\sin x}{\sqrt{x}} e^{-a x} dx=$$ Notice that $\displaystyle \frac{1}{\sqrt x}= \frac{2}{\sqrt{\pi}} \int_{0}^{\infty} e^{-xt^2} dt$ and have that

$$\frac{2}{\sqrt{\pi}} \int_{0}^{\infty} \sin x e^{-ax}\left(\int_{0}^{\infty} e^{-xt^2} dt\right) dx=$$ $$\frac{2}{\sqrt{\pi}} \int_{0}^{\infty} \left(\int_{0}^{\infty}\sin x e^{-(a+t^2)x} dt\right) dx=$$ Change the integration order $$\frac{2}{\sqrt{\pi}} \int_{0}^{\infty} \left(\int_{0}^{\infty}\sin x e^{-(a+t^2)x} dx\right) dt=$$ Now let's recollect the formula $$ \int e^{\alpha x} \sin (\beta x) \ dx = \frac{e^{\alpha x}(-\beta (\cos (\beta x) + \alpha \sin(\beta x)))}{{\alpha}^2+{\beta}^2}$$

Hence $$\int_{0}^{\infty}\sin x e^{-(a+t^2)x} dx=-\frac{e^{-(a+t^2)x}((a+t^2)\sin x + \cos x)}{1+(a+t^2)^2}\bigg|_{0}^{\infty}=\frac{1}{1+(a+t^2)^2}$$ Then $$\frac{2}{\sqrt{\pi}} \int_{0}^{\infty} \left(\int_{0}^{\infty}\sin x e^{-(a+t^2)x} dx\right) dt=\frac{2}{\sqrt{\pi}} \int_{0}^{\infty}\frac{1}{1+(a+t^2)^2} \ dt.$$ End of the relation $(1)$ proof.

Based upon the above relation we get that $$\int_0^{\infty} \frac{\sin x}{\sqrt{x}} dx=$$ $$ \lim_{a\to0+} \int_0^{\infty} \frac{\sin x}{\sqrt{x}} e^{-a x} dx =$$ $$ \lim_{a\to0+} \frac{2}{\sqrt{\pi}} \int_0^{\infty} \frac{1}{1+(a+x^2)^2} dx=$$ $$\frac{2}{\sqrt{\pi}} \int_0^{\infty} \frac{1}{1+x^4} dx \tag2$$ For the last integral we may change the variable and everything gets reduced to computing beta function

Change the variable $$x=\left(\frac{t}{1-t}\right)^{\frac{1}{4}}$$ Then $$\int_0^\infty \frac{1}{1+x^4} \ dx = \int_0^1 \frac{1}{4} (1-t)^{\frac{3}{4}-1} t^{\frac{1}{4}-1} \mathrm{d} t = \frac{1}{4} \operatorname{B}\left(\frac{1}{4}, \frac{3}{4}\right) = \frac{1}{4} \sqrt{2} \pi \tag3$$

Finally, from $(2)$ and $(3)$ we obtain the desired result

$$\int_0^\infty \frac{\sin x}{\sqrt{x}}dx=\sqrt{\frac{\pi}{2}}.$$ Q.E.D.

share|cite|improve this answer
Is it obvious what the result of the last indefinite integral is? – Pedro Tamaroff Jul 17 '12 at 19:15
Still, don't write "obviously" when you mean to say that somebody already did the work for you; it's better to link to the answer you refer to instead. – J. M. Jul 18 '12 at 11:21
@J. M.: agree. My answer was updated. – user 1618033 Jul 18 '12 at 11:33

Here I use Laplace Transform to present a simple proof and do not need use other tools. Note that $$ \int_0^\infty e^{-xt}\frac{1}{\sqrt{\pi t}}dt=\frac{1}{\sqrt x} $$ and hence \begin{eqnarray} \int_0^\infty\frac{\sin x}{\sqrt x}dx&=&\int_0^\infty\sin x\left(\int_0^\infty e^{-xt}\frac{1}{\sqrt{\pi t}}dt\right)dx\\ &=&\frac{1}{\sqrt\pi}\int_0^\infty \left(\int_0^\infty e^{-xt}\sin xdx\right) \frac{1}{\sqrt{t}}dt\\ &=&\frac{1}{\sqrt\pi}\int_0^\infty \frac{1}{t^2+1} \frac{1}{\sqrt{t}}dt\\ &=&\frac{1}{\sqrt\pi}\int_0^\infty \frac{\sqrt t}{t^2+1}dt\\ &=&\frac{1}{\sqrt\pi}\frac{\pi}{\sqrt 2}\\ &=&\sqrt{\frac{\pi}{2}}. \end{eqnarray} Here we use the following well-known integral $$ \int_0^\infty \frac{t^p}{t^2+1}dt=\frac{\pi}{2\cos\frac{p\pi}{2}}, |p|<1. $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.